Comparative analysis of metabolites and antioxidant potentials from different plant parts of Curcuma aeruginosa roxb - Sanimah Simoh,; Sew, Yun Shin; Fazri Abd Rahim,; Muhammad Aizuddin Ahmad,; Alizah Zainal, (Penerbit Universiti Kebangsaan Malaysia, 2018)
A comparative analysis of metabolites from different parts of Curcuma aeruginosa, i.e. leaves, stems, adventitious roots and rhizomes was performed by GC-MS/MS coupled with multivariate statistical analysis. The GC-MS/MS analysis confirmed the occurrence of 26 metabolites belonged to terpenoids in almost all the samples. The Principal Component Analysis (PCA) indicated that there was a clear distinction between rhizomes and other plant parts, i.e. stems, leaves, and adventitious roots that could be explained by relatively higher contents of terpenoids including curzerene, alpha-farnesen, furanocoumarin, velleral, germacrone cineole, borneol, beta- and gamma- elemene and methenolone. The results of Hierarchical Clustering Analyses (HCA) corresponded with the PCA results where many terpenoids found abundantly high in rhizome were clustered together. This was supported by the Pearson correlation analysis that showed a significantly good relationship between those terpenoids. The adventitious roots demonstrated the strongest antioxidant activity as compared to the other plant parts which could be attributed to its highest Total Phenolic Contents (TPC). Total phenolic contents of all the plant parts were positively correlated with their antioxidant activities which indicate that phenolic compounds may play a role in the overall antioxidant activities of the plants. The results of the study highlighted the potential of this underexploited Curcuma species which could serve as a new source of important phytochemicals and natural antioxidant that could be incorporated in functional foods and nutraceuticals. In addition, chemical and biological evidence shown in the present work has rationalised the different uses of various plant parts of C. aeruginosa.